Daily Use of Extra Virgin Olive Oil with High Oleocanthal Concentration Reduced Body Weight, Waist Circumference, Alanine Transaminase, Inflammatory Cytokines and Hepatic Steatosis in Subjects with the Metabolic Syndrome: A 2-Month Intervention Study - Patti, Angelo M.; Carruba, Giuseppe; Cicero, Arrigo F. G.; Banach, Maciej; Nikolic, Dragana; Giglio, Rosaria V.; Terranova, Antonino; Soresi, Maurizio; Giannitrapani, Lydia; Montalto, Giuseppe; Stoian, Anca Pantea; Banerjee, Yajnavalka; et al. (Metabolites, 2020)
Extra virgin olive oil (EVOO) intake is associated with reduced cardiovascular risk, and its phenolic compound oleocanthal (OC) has anti-oxidant and anti-inflammatory properties. The cardiometabolic effects of EVOO with a high OC concentration have not been fully elucidated. We administered EVOO with a high OC concentration daily to 23 subjects with the metabolic syndrome (MetS) and hepatic steatosis (15 men and 8 women, age: 60 ± 11 years) for 2 months. Anthropometric data, metabolic parameters, hepatic steatosis (by fatty liver index, FLI), abdominal fat distribution (by ultrasound), and pro- and anti-inflammatory cytokines were assessed before and after the intervention. EVOO supplementation was associated with a reduction in body weight, waist circumference, body mass index (BMI), alanine transaminase and FLI, as well as interleukin (IL)-6, IL-17A, tumor necrosis factor-α and IL-1B, while IL-10 increased. Maximum subcutaneous fat thickness (SFT max) also increased, with a concomitant decrease in the ratio of visceral fat layer thickness/SFT max. Correlation analysis revealed positive associations between changes in body weight and BMI and those in SFT max, along with an inverse association between changes in IL-6 and those in SFT max. In conclusion, ingestion of EVOO with a high OC concentration had beneficial effects on metabolic parameters, inflammatory cytokines and abdominal fat distribution in MetS subjects with hepatic steatosis, a category of patients at high cardiometabolic risk.